Effect of Soil Covering on CO2 Production and Cellulose Decomposition Activity - Varga, Csaba (Acta Agraria Debreceniensis, 2003)
In our experiments the effect of different soil cover matters (agroszövet and black polyethylene) on the CO2 production capacity and on the soil cellulose decomposition activity was studied. We also examined the relationship between the CO2 production and the cellulose decomposition activity. The trial was carried out in an apple plantation in Újfehértó. The CO2 production were determined after Witkamp with 5 days’ incubation period, the cellulose decomposition activity was measured according to Unger. Results showed that CO2 production and cellulose decomposition activity was higher in control soil almost in every cases. In respect of CO2 production the black polyethylene gave better values than the agroszövet.In 2000 the cellulose decomposition activity was significantly higher under covered soil than under uncovered every time. In spring of 2001 the controll but in summer and autumn agroszövet was significantly better. In summer and autumn black polyethylene prove non-significantly better than control. In average of two experimental years significantly higher cellulose decomposition activity was detected in covered soils than in control.In the most occassion a close connection was observed between cellulose decomposition activity and CO2 production. In spite of this the correlation was not significant in controll at all. Significant relationship was only found in spring and summer of 2001 under agroszövet, in spring and autumn of 2000 and in summer of 2001 under black polyethylene.